(3GdLed aj (B((3YhGed(B) (3GdEYQGHs - (3GdLQLGfj , YHO GdbGgQ Hf YHO GdQMef Hf eMeO, CHh HcQ,J (B471 (3g` s ((3CHhLYaQ CMeO Hf Ydj GdebQF GdHjgbj s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf MeO GdTGcQjf gPg Led QJHJgG JQJjHkG bQjH GdeJfGhd, hVefJgG LejY GdYhGed JgPH Pgf GdeHJOF hageg s
(3BNQgG (B:s
(3cbhdc RjO NQL ZdGeg, aGdgGA PcQ RjO dh bdJ RjO bGe YeQh de jLR hcPG GdHGbj agPG BNQ eG CQOfG ef GdLed aj YhGed GdEYQGH s
(3Vef eLehY , JQJjHgG (B: (3ef U (B108 - (3U(B121s
(3fSNI fbdgG Yf CUd deMeO Hf CHj GdaVd GdUGFZj GdHjgbjs
(3hHChdgG HNW GdfGSN Cf UGMH GdCUd bQC Ydjg gPG GdcJGH hHMK Yf eYGfjg HMKkG TOjOkGs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B48 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B310s
Keywords: (3GdfMhs